Development of Wall Panels Using Recycled Paper and Cotton Polyester Fibres for Acoustic and Thermal Performance - Irwan, Audra Irlyssa; Mohd Sari, Kamarul Aini; Kosnin, Hilmi (Progress in Engineering Application and Technology, 2022)
Noise pollution is one of the environmental problems that cannot be eliminated due to long-term exposure to excessive noise that can cause physical and psychological effects. In building application, an acoustic panel made of fibreglass or mineral wool materials is non-recyclable and poses health risks to occupants. Therefore, two recycled materials: paper and cotton polyester fibres, are used to produce panel boards. The study's objective is to identify the optimum proportion of recycled paper and cotton polyester fibres used in acoustic panels, measure the acoustic and thermal properties, and compare the properties with various materials from previous studies. The wall panels are made of 70% - 90% recycled paper with 10% - 30% cotton polyester fibres by wet mixing with natural tapioca binder composed of 100 g tapioca flour and 1000 mL water before being compressed using Gotech Testing Machine Hot Press Machine. Three samples were tested using an AED 1000 AcousticTube Impedance Tube and Solteq HE110 Thermal Conductivity Apparatus. The optimum proportion was 70% recycled paper 30% cotton polyester fibres. The results showed all samples had densities between 136.67 to 174.07 kg/m3 with sound absorption coefficients ranging from -0.70 to 0.04 and thermal conductivity k-values from 1.24 to 1.65 W/m °C. It was determined that composite material of recycled paper and cotton polyester fibres were poor quality material to use as acoustic panels because of the poor acoustic and thermal performance.